1985
DOI: 10.1038/bjc.1985.128
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α in benign and malignant breast tumours

Abstract: Prostaglandins (PGs), especially of the E-series, have been shown to be elevated in a large number of human and experimental tumours. Special efforts have been made to investigate the features and the role of PG-synthesis in human breast cancer (Bennett et al., 1975;Powles et al., 1976; Kibbey et al., 1980;Greaves et al., 1980;Malachi et al., 1981;Campbell et al., 1983).A considerable volume of research on the mechanisms of action of PGs in a wide variety of cells and tissues, indicates that PGs are possibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
1

Year Published

1987
1987
1991
1991

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 33 publications
3
18
1
Order By: Relevance
“…Tumour size Overall, the tumour size correlated inversely with PG-LM production, in agreement with Rolland et al (1980) who measured microsomal PGE2 formation from added arachidonic acid, with Fulton et al (1982) who measured endogenously formed PGE2, and with Vergote et al (1985) who found a similar tendency with PGF2a. In contrast, Karmali et al (1983) and Watson et al (1987) found no relationship between PGs and tumour size.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Tumour size Overall, the tumour size correlated inversely with PG-LM production, in agreement with Rolland et al (1980) who measured microsomal PGE2 formation from added arachidonic acid, with Fulton et al (1982) who measured endogenously formed PGE2, and with Vergote et al (1985) who found a similar tendency with PGF2a. In contrast, Karmali et al (1983) and Watson et al (1987) found no relationship between PGs and tumour size.…”
Section: Resultssupporting
confidence: 87%
“…However, Watson et al (1984) found similar yields of both PGE2 and PGF2,-Age Overall, the breast tumour total PG-LM correlates with age. Similar trends were seen for microsomal PGE2 formation (Rolland et al, 1980) or for PGF 2a production (Vergote et al, 1985), but Kibbey et al (1979) found no relationship to PGE2. Fulton et al (1982) obtained no correlation of PGE2 with age in just the post-menopausal women, whereas we did so with PG-LM in this group but not in premenopausal subjects.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations